2014
DOI: 10.1186/s12931-014-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin D deficiency is associated with frequent exacerbations and hospitalization in COPD patients

Abstract: BackgroundAcute exacerbations of COPD (AECOPD) are common and strongly influence disease severity and relative healthcare costs. Vitamin D deficiency is frequent among COPD patients and its contributory role in disease exacerbations is widely debated. Our aim was to assess the relationship of serum vitamin D levels with COPD severity and AECOPD.MethodsSerum vitamin D (25-hydroxyvitamin D) levels were measured in 97 COPD patients and related to lung function, comorbidities, FEV1 decline, AECOPD and hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 32 publications
4
53
0
3
Order By: Relevance
“…Since acute respiratory infections commonly precipitate exacerbations of both asthma and COPD, and it may be that protective effects of vitamin D against these outcomes are mediated by a common mechanism, namely induction of antiviral and antimicrobial responses. The protective effects demonstrated in this meta-analysis of intervention studies are consistent with results of some observational studies9 but at variance with others10: failure to demonstrate an association between vitamin D deficiency and increased exacerbation risk in some observational studies may relate to the low prevalence of participants with baseline 25(OH)D levels <25 nmol/L 23…”
Section: Discussionsupporting
confidence: 85%
“…Since acute respiratory infections commonly precipitate exacerbations of both asthma and COPD, and it may be that protective effects of vitamin D against these outcomes are mediated by a common mechanism, namely induction of antiviral and antimicrobial responses. The protective effects demonstrated in this meta-analysis of intervention studies are consistent with results of some observational studies9 but at variance with others10: failure to demonstrate an association between vitamin D deficiency and increased exacerbation risk in some observational studies may relate to the low prevalence of participants with baseline 25(OH)D levels <25 nmol/L 23…”
Section: Discussionsupporting
confidence: 85%
“…Vitamin D deficiency, in turn, has been associated with increased rates of exacerbations and hospitalization in COPD patients 8,9. Recent meta-analyses have concluded that vitamin D deficiency is directly associated with COPD disease severity and vitamin D supplementation may prevent exacerbations 1012.…”
Section: Introductionmentioning
confidence: 99%
“…An association between vitamin D deficiency and decreased pulmonary functions as well as airflow limitation in asthma patients has been suggested [6]. There have been some reports of the possible association of acute exacerbation of COPD with vitamin D deficiency although there have also been other reports that no association exists [7,8]. Martineau et al [9] reported that vitamin D 3 supplementation protected against moderate or severe exacerbation in subjects with COPD with low 25-hydroxyvitamin D [25(OH)D] level.…”
Section: Introductionmentioning
confidence: 99%